China in world politics policies, processes, prospects - Kornberg, Judith F. 1954-; Faust, John R. 1930-. (Boulder, Colo. Lynne Rienner Publishers, 2004)
"This fully revised text introduces students to China's foreign policy--past and present--and the factors that may influence the country's future policy agenda"--Provided by publisher.
First edition entered under author number "F38" for John R. Faust.
Keywords: China -- Foreign relations -- 1976-.; China -- Politics and government -- 1976-2002.; China -- Politics and government -- 2002-.